A Journey from Exterior to Interior in Hermann Hesse’s Siddartha - Dahal, Madhav Prasad (Haimaprabha, 2022)
This project tries to study the ways that lead Siddartha- a character in the novel of the same name by Hermann Hesse, to a state of liminality. It is a transitory moment in which a person realizes a perfect nothingness. It is a place neither outside nor inside, but a new journey starts from here. It is a phase in which a person forgets the present state of existence. It is a point of transition which is often accompanied by ritual. In the novel, Siddartha undergoes a situation in which his dissatisfaction with his present state of being leads him to meditate, through which he attains nothingness. This paper studies those moments of Siddhartha’s journey from the peripheral to the center from the perspective of Performance Studies. The finding of the study suggests that every one of us should try to find the essence of life within our own self for spiritual development. It makes a thematic analysis of the text with the insights of Turner Victor, Richard Schechner, Arnold Van, Tanya Goodman, Michelle Foucault, etc. It brings sources from the articles and books conceptually similar to Liminality or Transition.